2020
DOI: 10.3390/jcm9082634
|View full text |Cite
|
Sign up to set email alerts
|

Expression of Pinopodes in the Endometrium from Recurrent Pregnancy Loss Women. Role of Thrombomodulin and Ezrin

Abstract: Background: Pinopode expression has been suggested as a marker of endometrial receptivity. Methods: We set up an experimental study comparing endometrial tissue from recurrent pregnancy loss (RPL, n = 30) and fertile control (CTR, n = 20) women in terms of pinopode expression/morphology; expression of thrombomodulin (TM) and ezrin; cytoskeletal organization. Endometrial samples were collected during implantation window and evaluated by scanning electron microscopy, western blot, and immunofluorescence. Results… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 49 publications
0
16
0
Order By: Relevance
“…Pinopodes seem to be a useful maker for endometrium receptivity in many species 33,34 . In this study, the SEM observation showed that the number of pinopodes was significantly different between agomir NC group and miR‐100‐5p agomir group.…”
Section: Discussionmentioning
confidence: 48%
See 1 more Smart Citation
“…Pinopodes seem to be a useful maker for endometrium receptivity in many species 33,34 . In this study, the SEM observation showed that the number of pinopodes was significantly different between agomir NC group and miR‐100‐5p agomir group.…”
Section: Discussionmentioning
confidence: 48%
“…32 Our study also verified that overexpressed circ-9110 promoted ESCs Pinopodes seem to be a useful maker for endometrium receptivity in many species. 33,34 In this study, the SEM observation showed that the number of pinopodes was significantly different between agomir NC group and miR-100-5p agomir group. The number of pinopodes and length of microvilli in miR-100-5p agomir group significantly decreased compared with agomir NC group.…”
Section: Con Clus Ionmentioning
confidence: 52%
“…Although previously controversial, recent literature has deemed the presence of pinopodes in the endometrial epithelia as a credible biomarker of uterine receptivity [52, 54]. Filamentous actin expression coincides with pinopode formation during receptivity on the apical surface of luminal epithelial cells [55]. In the endometria of from those suffering recurrent pregnancy loss, both ezrin and thrombomodulins were downregulated which disrupted the organisation of cytoskeletal actin filaments and may ultimately impaired pinopode formation.…”
Section: Discussionmentioning
confidence: 99%
“…In the initial stage of pregnancy, TM is involved in embryonic implantation by maintaining the cytoskeletal organization of endometrial cells. 57 TM is identified on the endometrium, which is modified into decidua during placentation. Endometrial TM connects to actin filaments via bridging protein ezrin, which is responsible for cell-to-cell adhesion and cytoskeletal development.…”
Section: Function Of Tm During Pregnancymentioning
confidence: 99%